Financial Sustainable Growth Theory as a Result of Interaction with Energy, Environmental and Social Processes (Evidence from Oil and Gas Industry) - A. N. Steblyanskaya; Zhen Wang; Z. V. Bragina (Финансы: теория и практика, 2019)
The research is based on the materials of the largest oil and gas companies in Russia and China, whose total production in each country exceeds 86%. The authors used indicators that are available to the world statistics and relate to the system of sustainable financial growth in Russia and China from 1996 to 2016. The aim of the article is to study the impact of investments in personnel social welfare, energy efficiency and environmental protection on sustainable financial growth of the oil and gas industry. The research objectives are to develop a theory of sustainable financial growth in the oil and gas industry, as well as its assessment and forecasting tools. The authors use the methods of statistical analysis of financial, social, energy and environmental coefficients, and mathematical modeling. They propose a new methodology for calculating the index of the financial sustainable growth system. The authors substantiate the composition and the structure of the sustainable financial growth system of oil and gas companies in Russia and China, as well as the composition of the economic processes that influence or predetermine this growth. The relationship between the subsystem indicators were analyzed in the article. The article substantiates the index of the sustainable financial growth system of oil and gas companies in Russia and China. The authors developed a model for calculating the index of the sustainable financial growth system in the AnyLogic program. The results of the study showed that the factors of the “energy efficiency” and “social subsystem” subsystems affect financial sustainable growth in Russian oil and gas companies, but the financial subsystem is least dependent on the “environment” subsystem. The situation in Chinese oil and gas companies is the opposite: the financial sustainable growth is mostly affected by the factors of the “environment” and “energy efficiency” subsystems. The financial subsystem is least connected with the subsystem of personnel social welfare. Nevertheless, the study proves that in the oil and gas companies in both countries, nonfinancial indicators (each country has its own block) have a positive effect on the financial sustainable growth. According to the authors, the main conclusion is to consider social, energy and environmental indicators that have the strongest influence on the financial sustainable growth in the company’s financial statements. The developed AnyLogic model can be used to predict the index of the sustainable growth system and its management. The results of the study are recommended for the oil and gas corporations of China.